Calcium carbonate suspension as well as preparation method and application thereof

By mixing specific inorganic fillers with calcium carbonate to form a calcium carbonate suspension, the problem of poor fluidity of the calcium carbonate solution is solved, the effect of high fluidity and high retention is achieved, and the quality of tobacco flakes is improved.

CN119699637APending Publication Date: 2025-03-28SHANGHAI TOBACCO GROUP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411869562.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, calcium carbonate solution is prone to stratification, precipitation and material blockage during the production process of re-engineering tobacco leaves, resulting in poor fluidity and affecting production efficiency and product quality.

Method used

By mixing specific inorganic fillers (such as talc, silica powder, barium sulfate, kaolin and titanium dioxide) with calcium carbonate in a specific proportion, it forms a calcium carbonate suspension to improve its fluidity. This method changes its structure by adsorbing inorganic fillers onto the surface of calcium carbonate, thereby reducing the consistency and improving fluidity.

Benefits of technology

The fluidity and retention rate of calcium carbonate solution are significantly improved, the consistency is reduced, the risk of filler deposition is reduced, and the bulk thickness and retention rate of tobacco flakes are increased.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005195421290000061
    Figure BDA0005195421290000061
  • Figure BDA0005195421290000071
    Figure BDA0005195421290000071
  • Figure BDA0005195421290000072
    Figure BDA0005195421290000072
Patent Text Reader

Abstract

The invention discloses a calcium carbonate suspension as well as a preparation method and application thereof. The calcium carbonate suspension comprises calcium carbonate, an inorganic filler and a solvent, the mass ratio of the calcium carbonate to the inorganic filler is (3-19): 1, and the inorganic filler is selected from one or more of talcum powder, silica powder, barium sulfate, kaolin and titanium dioxide. The inorganic filler, the calcium carbonate and the solvent are mixed to obtain the calcium carbonate suspension, compared with calcium carbonate slurry formed by the calcium carbonate and the solvent, the calcium carbonate suspension has the advantages that the consistency is obviously reduced, the fluidity is better, and the problems that the calcium carbonate slurry is easy to aggregate, precipitate and layer and block a pipeline tank body are solved; and the retention rate and the bulkiness of the tobacco sheets obtained by taking the tobacco leaves as the raw materials are higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tobacco, and in particular relates to a calcium carbonate suspension and a preparation method and application thereof. Background Art

[0002] With the increasing positive effects of paper-made reconstituted tobacco on improving cigarette structure, reducing tar and reducing harm in recent years, paper-made reconstituted tobacco has become an important and indispensable raw material for Chinese cigarettes. In the production process of reconstituted tobacco, calcium carbonate is a commonly used inorganic filler, which is generally used in tobacco sheet base and / or tobacco coating liquid. It can not only improve the bulk, water absorption and ash content of reconstituted tobacco, but also improve the whiteness and fire retention of ash after burning, thereby indirectly affecting the burning speed of reconstituted tobacco and the release of harmful substances in smoke.

[0003] During the production process, calcium carbonate fillers need to be prepared into a 35-45% high concentration solution. Due to the polarity of the surface of calcium carbonate particles, after being prepared into a solution, the particles interact with each other, causing the fillers to aggregate into clusters, resulting in filler stratification, precipitation, and blockage in the preparation tank. Considering the feasibility of on-site filler solution transportation and the risk of filler deposition in pipeline tanks, the calcium carbonate solution needs to maintain excellent fluidity.

[0004] The conventional method to improve the fluidity of calcium carbonate is to add dispersants to reduce the polarity of the filler surface, thereby reducing the interaction between fillers, but the economic cost is high and may affect the sensory taste of reconstituted tobacco. Related literature also mentioned that under certain conditions, the use of inorganic substances to modify the filler can significantly improve the retention performance of the filler. Commonly used inorganic substances in papermaking include hydrogen fluoride, sodium hexametaphosphate, barium chloride, phosphoric acid, etc. ZhangHT et al. modified talcum powder using Al2O3 and P2O5, and found that 2.5% Al2O3 and 2.5% P2O5 mixed modified talcum powder has a better retention effect than 5% Al2O3 alone modified talcum powder. Among them, when the amount of filler added is 30%, the retention rate of the compound modified talcum powder can be increased by 30% compared with the single modified talcum powder.

[0005] However, in actual applications, Al2O3 and P2O5 are both industrial-grade raw materials that do not meet the food-grade safety requirements for tobacco additions. At the same time, experimental verification has shown that these two fillers cannot effectively improve the fluidity of calcium carbonate. Therefore, a method for improving the fluidity of calcium carbonate solution is urgently needed. Summary of the invention

[0006] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a calcium carbonate suspension and a preparation method and use thereof, so as to solve the problems existing in the prior art.

[0007] To achieve the above objectives and other related objectives, the present invention is achieved through the following technical solutions.

[0008] One of the purposes of the present invention is to provide a calcium carbonate suspension, comprising calcium carbonate, an inorganic filler and a solvent, wherein the mass ratio of the calcium carbonate to the inorganic filler is (3-19):1, and the inorganic filler is selected from one or more of talc, silica powder, barium sulfate, kaolin and titanium dioxide.

[0009] After a long period of extensive experimental research, the present invention has found that mixing a specific inorganic filler with calcium carbonate in a certain proportion can improve the fluidity of calcium carbonate after it is dissolved in a solvent. The reason may be that the fine particles of inorganic filler are adsorbed on the surface of calcium carbonate and wrap the calcium carbonate, so that the calcium carbonate particles change from a spindle shape to a spherical porous structure, achieving the effect of surface modification of calcium carbonate, thereby improving the fluidity or consistency of calcium carbonate after it is dissolved in a solvent. In addition, adding the calcium carbonate suspension of the present application to the tobacco coating liquid to obtain a tobacco sheet or adding it to the tobacco coating liquid can not only effectively improve the retention rate of calcium carbonate in the tobacco sheet or tobacco base paper, but also improve the bulk.

[0010] In certain embodiments, the mass ratio of calcium carbonate to inorganic filler can be (3-19):1, (3-10):1, (8-15):1, (14-19):1, or 3:1, 5:1, 7:1, 9:1, 11:1, 13:1, 15:1, 17:1, or 19:1.

[0011] In certain embodiments, the calcium carbonate is selected from light calcium carbonate. The light calcium carbonate in the present application complies with the provisions of GB1886.214 "Food Safety National Standard Food Additive Calcium Carbonate".

[0012] In certain embodiments, the calcium carbonate has a particle size of 1 to 10 μm.

[0013] In certain embodiments, the particle size of the inorganic filler is ≤61 μm.

[0014] In some specific embodiments, the particle size of the talc is 2 to 6 μm.

[0015] In some specific embodiments, the silica powder has a particle size of 0.1 to 0.3 μm.

[0016] In some specific embodiments, the particle size of the barium sulfate is 0.1-0.5 μm.

[0017] In some specific embodiments, the particle size of the kaolin is 0.20-0.25 μm.

[0018] In some specific embodiments, the particle size of the titanium dioxide is ≤61 μm.

[0019] In certain embodiments, the solvent is selected from one or both of water and ethanol.

[0020] In certain embodiments, a solvent is further included; based on the total mass of the inorganic filler, calcium carbonate and the solvent, the total mass concentration of the inorganic filler and calcium carbonate is not less than 35 wt %.

[0021] In some specific embodiments, based on the total mass of the inorganic filler, calcium carbonate and the solvent, the total content of the inorganic filler and calcium carbonate is 35-55wt%, or may be 35wt%, 40wt%, 45wt% and 55wt%.

[0022] In some embodiments, the consistency of the calcium carbonate suspension is reduced by at least 7% compared to the mixture formed by calcium carbonate and solvent. In some specific embodiments, it can be 7% to 50%, 7% to 25%, 20% to 36%, or 32% to 50%.

[0023] A second aspect of the present invention is to provide a method for preparing the calcium carbonate suspension as described above, comprising the steps of:

[0024] The inorganic filler, calcium carbonate and solvent are mixed to obtain the calcium carbonate suspension.

[0025] In some embodiments, inorganic filler and solvent are mixed for the first time to obtain inorganic filler slurry, and then mixed for the second time with calcium carbonate, dried to obtain the calcium carbonate suspension. The application has been found through research that inorganic filler and solvent are first mixed, and then calcium carbonate is added to separate, and fluidity is better. In production, when configuring high-concentration pure calcium carbonate solution, without using inorganic filler, the dispersibility and fluidity of filler are very poor, and very solution precipitation, once precipitated, can block the bottom of the tank and pipeline, and is difficult to clean. At this time, inorganic filler particles are added again, and under ultra-high concentration conditions, the problem of filler blocking can not be solved. But when solvent and inorganic filler are first mixed to form inorganic filler slurry, the properties such as hydrogen bonds, electric charge in the slurry are all different from solvent, and then calcium carbonate is added, which can effectively reduce the precipitation of calcium carbonate and increase fluidity.

[0026] In some specific embodiments, the temperature of the first mixing is 30-50°C, or 30-42°C, or 38-46°C, or 42-50°C.

[0027] In some specific embodiments, the first mixing time is 5 to 15 minutes, or 5 to 9 minutes, or 8 to 12 minutes, or 10 to 15 minutes.

[0028] In some specific embodiments, the temperature of the second mixing is 30-50°C, or 30-42°C, or 38-46°C, or 42-50°C.

[0029] In some specific embodiments, the second mixing time is 5 to 40 min, or 5 to 25 min, or 20 to 32 min, or 25 to 40 min.

[0030] A third aspect of the present invention protects the use of the calcium carbonate suspension as described above as a raw material in tobacco sheets.

[0031] A fourth aspect of the present invention protects a tobacco sheet comprising a tobacco base paper, wherein the tobacco base paper comprises the calcium carbonate suspension as described above.

[0032] In certain embodiments, the method for preparing the tobacco-based paper is: mixing tobacco raw materials and water and extracting to obtain a solid phase mixture; pulping the solid phase mixture to obtain tobacco slurry, and papermaking to obtain tobacco-based paper; adding the calcium carbonate suspension described above to the tobacco slurry.

[0033] In some specific embodiments, the amount of calcium carbonate suspension added is 7-13% based on the absolute dry weight of the tobacco slurry. In a specific embodiment, it is 10%.

[0034] In some specific embodiments, the beating degree of the tobacco slurry is 50-65°SR. In a specific embodiment, it is 52°SR. The beating degree determination method in this application is carried out in accordance with GB / T 3332-2004.

[0035] In some specific embodiments, the temperature during the extraction is 50°C to 100°C. In a specific embodiment, it is 65°C.

[0036] In some specific embodiments, the solid-liquid ratio during the extraction is 1g:(4-8)g. In a specific embodiment, it is 1g:6g, that is, the mass ratio of tobacco raw material to water is 1g:6g.

[0037] In certain embodiments, the method further comprises a tobacco coating liquid, wherein the tobacco coating liquid comprises the calcium carbonate suspension as described above.

[0038] In some specific embodiments, the tobacco coating liquid further comprises a tobacco extract, and the mass ratio of the tobacco extract to the calcium carbonate suspension is 100:(3-10). In a certain embodiment, it is 100:7.

[0039] In some more specific embodiments, the density of the tobacco extract is 0.5 to 2 g / cm3 In one embodiment, 1.185 g / cm 3 .

[0040] In some more specific embodiments, the tobacco extract is prepared by mixing tobacco raw materials and water and extracting to obtain a solid phase mixture and a liquid phase mixture; and concentrating the liquid phase mixture to obtain the tobacco extract.

[0041] Preferably, the tobacco raw material is selected from one or more of tobacco stems, tobacco flakes and tobacco dust.

[0042] Preferably, the temperature during the extraction is 50°C to 100°C. In a specific embodiment, it is 65°C.

[0043] Preferably, the solid-liquid ratio during the extraction is 1g:(4-8)g. In a specific embodiment, it is 1g:6g, that is, the mass ratio of tobacco raw material to water is 1g:6g.

[0044] In one embodiment, the tobacco sheet is obtained by coating a tobacco coating liquid containing a calcium carbonate suspension on a tobacco base paper containing a calcium carbonate suspension. Preferably, the coating rate is 20-40%, or 20-35%, or 30-40%, or 25%, 30%, 38%, or 40%.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] After long-term research, the inventors found that the calcium carbonate suspension obtained by mixing a specific inorganic filler and calcium carbonate not only has a concentration of more than 35%, but also has low viscosity, good fluidity, and no stratification; compared with the calcium carbonate slurry formed by calcium carbonate and solvent, the viscosity of the calcium carbonate suspension is reduced by 18% to 46%, reducing the risk of filler deposition in pipeline tanks. Adding it to tobacco extract to form a tobacco coating liquid or adding it to tobacco slurry to form tobacco base paper can improve the retention rate and bulk of tobacco sheets. The reason for the high fluidity of the calcium carbonate suspension of the present invention may be that the inorganic filler is adsorbed on the surface of calcium carbonate, eliminating the bonding force of calcium carbonate particles, avoiding "agglomeration" of particles, and achieving excellent fluidity of high-concentration calcium carbonate solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 Shown is a scanning electron microscope image of the tobacco sheet obtained in Example 1 of the present invention.

[0048] Figure 2 Shown is a real shot of the calcium carbonate suspension of Example 6 of the present invention.

[0049] Figure 3 Shown is a real picture of the tobacco coating liquid of Example 6 of the present invention. DETAILED DESCRIPTION

[0050] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0051] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods in the following examples without specifying specific conditions are generally carried out under conventional conditions or under conditions recommended by the manufacturers.

[0052] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.

[0053] The applicant has explored the mass ratio of inorganic filler to calcium carbonate and the particle size of inorganic filler. When the mass ratio of calcium carbonate to inorganic filler in the present application is (2-21):1, the consistency of the obtained calcium carbonate suspension is the best. For example, taking silica powder as an example, when the mass ratio of calcium carbonate to silica powder exceeds 21:1 and is 22:1, the consistency of the obtained calcium carbonate suspension is 736.7g.sec. Under this condition, the proportion of silica powder in the filler mixture is too low and cannot play a role in increasing the fluidity of the calcium carbonate suspension. When the mass ratio of calcium carbonate to silica powder is lower than 2:1, the obtained calcium carbonate suspension has a viscosity of 417.3 g.sec. Although the viscosity of the calcium carbonate suspension meets the requirements, too much silica powder is introduced into the suspension, resulting in the addition ratio of silica powder exceeding the set requirements when the same calcium carbonate ratio is added to the product. Experimental studies have shown that when the silica powder content in the flakes is too high, it will affect the product's taste. In addition, the particle size of the inorganic filler will also affect the viscosity of the suspension. Taking silica powder as an example, when the particle size of silica powder exceeds 6 μm, the effect on the calcium carbonate suspension is weakened, resulting in a calcium carbonate suspension with a viscosity of 679.5 g.sec. The fluidity of the calcium carbonate suspension does not meet the requirements of production and use.

[0054] In order to further illustrate the above-mentioned synthesis method of the present application and the technical effects achieved therein, the following examples are used for further explanation and illustration.

[0055] All raw materials in this application have no special restrictions on their sources and can be obtained through commercial channels.

[0056] Example 1

[0057] In this embodiment 1, silica powder is used as an inorganic filler and water is used as a solvent to prepare and obtain a calcium carbonate suspension, including the following:

[0058] 1.1. Selection of silica powder particle size

[0059] 1) With a mass ratio of calcium carbonate / inorganic filler of 3:1, silica powder of different particle sizes was weighed according to Table 1, and the silica powder of different particle sizes was respectively mixed with water at 30° C. for the first time for 5 min to prepare a silica powder slurry; based on the total mass of silica powder and water, the mass concentration of silica powder in the silica powder slurry was 1wt%.

[0060] 2) Weigh 1 kg of light calcium carbonate with a particle size of 1 μm and 1.85 kg of silica powder slurry from step 1) and stir and mix them for a second time at 30° C. for 5 min to prepare a calcium carbonate suspension; based on the total mass of the inorganic filler, calcium carbonate and solvent, the total mass concentration of the inorganic filler and calcium carbonate in the calcium carbonate suspension is 35 wt %.

[0061] At the same time, water and light calcium carbonate with a particle size of 1 μm were mixed at 30° C. for 5 minutes to prepare a calcium carbonate slurry as the 1# control group; based on the total mass of calcium carbonate and the solvent, the mass concentration of calcium carbonate in the calcium carbonate slurry was 35wt%.

[0062] The consistency was measured and the results are shown in Table 1.

[0063] Table 1

[0064]

[0065] As can be seen from Table 1, the addition of silica powder of different particle sizes will lead to a decrease in the consistency of the calcium carbonate suspension. Compared with the calcium carbonate slurry formed by mixing calcium carbonate and water, the consistency of the calcium carbonate suspension is reduced by 8.20-26.76%; when the particle size of the added silica powder is 0.1-0.3 μm, the consistency of the calcium carbonate suspension is significantly reduced to 26.76%.

[0066] Viscosity: The properties of the calcium carbonate solution were tested using a TA texture analyzer (Stable Micro System Ltd, UK), Probe: P / 36R, Test Mode: Compression; Pre-Test Speed: 1 mm / s; Test Speed: 1 mm / s; Post-Test Speed: 5 mm / s; Distance: 15 mm; Trigger Force: 2 g; the test data was the average value of three groups of samples.

[0067] The texture analyzer includes a host, special software, spare probes and accessories. Its basic structure is generally composed of a mechanical device that can deform the sample and a recording system that records the force, time and deformation rate. Place the liquid in the measuring cup. The liquid level generally does not exceed 75% of the measuring cup, and the pressing depth should not exceed 75% of the liquid depth to avoid collision with the bottom of the cup. Starting from the starting position, the probe first presses toward the test sample at a set rate. After contacting the surface of the sample, it compresses the sample at a certain distance at the test rate, and then returns to the starting point of the compression. Finally, it returns to the position before the probe is measured at a set rate.

[0068] 1.2. Selection of the ratio of silica powder and calcium carbonate

[0069] i) With the mass ratio of calcium carbonate to silica powder as shown in Table 2, silica powder with a particle size of 0.2 μm and water were stirred and mixed for the first time at 40° C. for 10 min to prepare a silica powder slurry; based on the total mass of silica powder and water, the mass concentration of silica powder was 6 wt %.

[0070] ii) weighing 1 kg of light calcium carbonate with a particle size of 1 μm and 1.5 kg of the silica powder slurry obtained in step i), stirring and mixing for a second time at 40° C. for 20 min to prepare a calcium carbonate suspension; based on the total mass of the inorganic filler, calcium carbonate and the solvent, the total mass concentration of the inorganic filler and calcium carbonate in the calcium carbonate suspension is 40 wt %.

[0071] At the same time, water and light calcium carbonate with a particle size of 1 μm were mixed for 20 minutes to prepare calcium carbonate slurry, which was used as the 2# control group; based on the total mass of calcium carbonate and solvent, the mass concentration of calcium carbonate in the calcium carbonate slurry was 40wt%.

[0072] The consistency was measured and the results are shown in Table 2.

[0073] Table 2

[0074]

[0075] As can be seen from Table 2, the addition of silica powder in different proportions will lead to a decrease in the consistency of the calcium carbonate suspension. Compared with the calcium carbonate slurry formed by mixing calcium carbonate and water, the consistency of the calcium carbonate suspension is reduced by 8.94% to 46.01%; when the mass ratio of light calcium carbonate to silica powder is 19:1-2:1, the consistency of the calcium carbonate suspension is most significantly reduced, with a reduction of about 26.22%-46.01%, among which when the mass ratio of light calcium carbonate to silica powder is 3:1, the maximum reduction in consistency is 46.01%.

[0076] 1.3. Adding calcium carbonate suspension to tobacco flakes

[0077] The calcium carbonate suspensions of different mass concentrations obtained in step 1.2 were added to the tobacco slurry to prepare tobacco base paper, and further prepared tobacco sheets. The retention rate and bulk were tested. The results are shown in Table 3.

[0078] At the same time, the 40% calcium carbonate slurry obtained in step 1.2 (i.e., the 2# control group) was added to the tobacco slurry in the same manner to prepare tobacco base paper, and then further prepared tobacco sheets (i.e., the control sample). The retention rate and bulk were checked. The results are shown in Table 3.

[0079] The preparation method of tobacco flakes is as follows: tobacco stems, tobacco flakes and tobacco dust are uniformly mixed in a mass percentage of 50%:30%:20% to obtain a mixed tobacco raw material, and 65°C hot water is added according to a mass ratio of the mixed tobacco raw material to water of 1:6 for extraction for 40 minutes; after the extraction is completed, the material is mechanically squeezed for solid-liquid separation, and the solid phase extract is processed by a pulping process to prepare a tobacco slurry, and the beating degree of the tobacco slurry is 52°SR, and then the calcium carbonate suspension of Example 1 is added to the tobacco slurry at 10% of the absolute dry weight of the tobacco slurry, and then based on the papermaking process, tobacco base paper is produced and prepared, and the base paper has a basis weight of 60g / m 2 The liquid tobacco extract was concentrated and dehydrated to produce a density of 1.185 g / cm 3 The tobacco coating liquid is then applied to the surface of the tobacco base paper at a coating rate of 38%, and finally dried at 120° C. for 3 min to obtain a tobacco sheet.

[0080] The preparation method of the control sample is the same as above, except that calcium carbonate slurry is used instead of calcium carbonate suspension.

[0081] Table 3

[0082]

[0083] It can be seen from Table 3 that when the mass ratio of light calcium carbonate to silica powder is (2-19):1, the retention rate and bulk of the prepared tobacco sheet are relatively high; among them, when the mass ratio of light calcium carbonate to silica powder is 3:1, the retention rate and bulk are the highest.

[0084] Scanning electron microscopy observation of tobacco slices revealed that calcium carbonate with a spherical porous structure was attached to the surface, with a particle size of 20 μm.

[0085] Example 2

[0086] In this Example 2, talcum powder is used as an inorganic filler and water is used as a solvent to prepare and obtain a calcium carbonate suspension, including the following:

[0087] 1) With a mass ratio of calcium carbonate / inorganic filler of 6:1, talcum powder of different particle sizes was weighed according to Table 4, and the talcum powder of different particle sizes was respectively mixed with water at 30° C. for the first time for 5 min to prepare a talcum powder slurry; based on the total mass of talcum powder and water, the mass concentration of talcum powder in the talcum powder slurry was 1wt%.

[0088] 2) Weighing 1 kg of light calcium carbonate with a particle size of 1 μm and 1.85 kg of talc slurry from step 1) and stirring and mixing them for a second time at 30° C. for 5 min to prepare a calcium carbonate suspension; based on the total mass of the inorganic filler, calcium carbonate and solvent, the total mass concentration of the inorganic filler and calcium carbonate in the calcium carbonate suspension is 35 wt %.

[0089] Meanwhile, the calcium carbonate slurry obtained in step 1.1 of Example 1 was used as a control.

[0090] The consistency was measured and the results are shown in Table 4.

[0091] Table 4

[0092]

[0093] As can be seen from Table 4, the addition of talcum powder of different particle sizes will lead to a decrease in the consistency of the calcium carbonate suspension. Compared with the calcium carbonate slurry formed by mixing calcium carbonate and water, the consistency of the calcium carbonate suspension is reduced by 7.11-18.97%; when the particle size of the added talcum powder is 2-6 μm, the consistency of the calcium carbonate suspension is significantly reduced to 18.97%.

[0094] The same method as in Example 1 was used to add the tobacco material to prepare tobacco sheets.

[0095] Scanning electron microscopy observation of tobacco slices revealed that calcium carbonate with a spherical porous structure was attached to the surface, with a particle size of 27 μm.

[0096] Example 3

[0097] In this embodiment 3, barium sulfate is used as an inorganic filler and water is used as a solvent to prepare and obtain a calcium carbonate suspension, including the following:

[0098] 1) With a mass ratio of calcium carbonate / inorganic filler of 19:1, barium sulfate of different particle sizes was weighed according to Table 5, and the barium sulfate of different particle sizes was respectively mixed with water at 30° C. for the first time for 5 minutes to prepare barium sulfate slurry; based on the total mass of barium sulfate and water, the mass concentration of barium sulfate in the barium sulfate slurry was 1wt%.

[0099] 2) Weigh 1 kg of light calcium carbonate with a particle size of 1 μm and 1.22 kg of barium sulfate slurry from step 1) and stir and mix them for a second time at 30° C. for 5 min to prepare a calcium carbonate suspension; based on the total mass of the inorganic filler, calcium carbonate and solvent, the total mass concentration of the inorganic filler and calcium carbonate in the calcium carbonate suspension is 45 wt %.

[0100] At the same time, water and light calcium carbonate with a particle size of 1 μm were stirred and mixed at 30° C. for 5 minutes to prepare a calcium carbonate slurry as the 3# control group; based on the total mass of calcium carbonate and the solvent, the mass concentration of calcium carbonate in the calcium carbonate slurry was 45wt%.

[0101] The consistency was measured and the results are shown in Table 5.

[0102] Table 5

[0103]

[0104] As can be seen from Table 5, the addition of barium sulfate with different particle sizes will lead to a decrease in the consistency of the calcium carbonate suspension. Compared with the calcium carbonate slurry formed by mixing calcium carbonate and water, the consistency of the calcium carbonate suspension is reduced by 19.51-24.56%; when the particle size of the added barium sulfate is 0.1-0.3 μm, the consistency of the calcium carbonate suspension is reduced to 24.56%.

[0105] The tobacco sheet prepared by adding the tobacco material in the same manner as in Example 1 was prepared.

[0106] Scanning electron microscopy observation of tobacco slices revealed that calcium carbonate with a spherical porous structure was attached to the surface, with a particle size of 43 μm.

[0107] Example 4

[0108] In this Example 4, kaolin is used as an inorganic filler and water is used as a solvent to prepare and obtain a calcium carbonate suspension, including the following:

[0109] 1) With a mass ratio of calcium carbonate / inorganic filler of 10:1, kaolin of different particle sizes were weighed according to Table 6, and the kaolin of different particle sizes were respectively stirred and mixed with water at 30° C. for 5 min to prepare kaolin slurry; based on the total mass of kaolin and water, the mass concentration of barium sulfate in the kaolin slurry was 1wt%.

[0110] 2) Weigh 1 kg of light calcium carbonate with a particle size of 1 μm and 1.85 kg of kaolin slurry from step 1) and stir and mix them for a second time at 30° C. for 5 min to prepare a calcium carbonate suspension; based on the total mass of the organic filler, calcium carbonate and solvent, the total mass concentration of the inorganic filler and calcium carbonate in the calcium carbonate suspension is 35 wt %.

[0111] Meanwhile, the calcium carbonate slurry obtained in step 1.1 of Example 1 was used as a control.

[0112] The viscosity was measured and the results are shown in Table 6.

[0113] Table 6

[0114]

[0115] As can be seen from Table 6, the addition of kaolin with different particle sizes will lead to a decrease in the consistency of the calcium carbonate suspension. Compared with the calcium carbonate slurry formed by mixing calcium carbonate and water, the consistency of the calcium carbonate suspension is reduced by 13.26-18.70%; when the particle size of the added kaolin is 0.2-0.3 μm, the consistency of the calcium carbonate suspension is significantly reduced to 18.70%.

[0116] The tobacco sheet prepared by adding the tobacco material in the same manner as in Example 1 was prepared.

[0117] Scanning electron microscopy observation of tobacco slices revealed that calcium carbonate with a spherical porous structure was attached to the surface, with a particle size of 27 μm.

[0118] Example 5

[0119] In this embodiment 1, titanium dioxide is used as an inorganic filler and water is used as a solvent to prepare and obtain a calcium carbonate suspension, including the following:

[0120] 1) With a mass ratio of calcium carbonate / inorganic filler of 10:1, titanium dioxide of different particle sizes was weighed according to Table 7, and the titanium dioxide of different particle sizes was respectively stirred and mixed with water at 30° C. for a first time for 5 minutes to prepare a titanium dioxide slurry; based on the total mass of titanium dioxide and water, the mass concentration of titanium dioxide in the titanium dioxide slurry was 1wt%.

[0121] 2) Weigh 1 kg of light calcium carbonate with a particle size of 1 μm and 1.85 kg of titanium dioxide slurry from step 1) and stir and mix them for a second time at 30° C. for 5 min to prepare a calcium carbonate suspension; based on the total mass of the inorganic filler, calcium carbonate and solvent, the total mass concentration of the inorganic filler and calcium carbonate in the calcium carbonate suspension is 35 wt %.

[0122] Meanwhile, the calcium carbonate slurry obtained in step 1.1 of Example 1 was used as a control.

[0123] The consistency was measured and the results are shown in Table 8.

[0124] Table 8

[0125]

[0126] As can be seen from Table 8, the addition of titanium dioxide with different particle sizes will lead to a decrease in the consistency of the calcium carbonate suspension. Compared with the calcium carbonate slurry formed by mixing calcium carbonate and water, the consistency of the calcium carbonate suspension is reduced by 15.23% to 32.30%; when the particle size of the added titanium dioxide is 1 to 3 μm, the calcium carbonate suspension is significantly reduced by 32.30%.

[0127] The tobacco sheet prepared by adding the tobacco material in the same manner as in Example 1 was prepared.

[0128] Scanning electron microscopy observation of tobacco slices revealed that calcium carbonate with a spherical porous structure was attached to the surface, with a particle size of 27 μm.

[0129] The calcium carbonate suspension obtained in each of Examples 1-5 was selected with the highest consistency and added to the tobacco slurry to prepare tobacco base paper and tobacco flakes. The preparation method of tobacco flakes is the same as that in Example 1.

[0130] Control group 1 and control group 2: Water and light calcium carbonate with a particle size of 1 μm were mixed for 5 minutes to prepare 35% and 45% pure calcium carbonate slurries, respectively. The 35% and 45% pure calcium carbonate slurries were added to the tobacco slurry, respectively, to prepare tobacco base paper and tobacco sheets, which were used as control group 1 and control group 2. The preparation method was the same as that of Example 1.

[0131] from Figure 1 As can be seen from the middle right figure, after drying, the tobacco slices were observed using a scanning electron microscope, and it was found that the calcium carbonate attached to the surface of the tobacco slices of Example 1 was in a spherical porous structure.

[0132] from Figure 1 As can be seen from the middle left figure, after drying, the tobacco slices were observed using a scanning electron microscope, and it was found that the calcium carbonate attached to the surface of the tobacco slices of the control group 1 was a spindle-shaped structure.

[0133] The retention rate and bulk of Examples 1-5, Control Group 1 and Control Group 2 were tested. The results are shown in Table 9.

[0134] Table 9

[0135]

[0136] As can be seen from Table 9, compared with the tobacco sheet samples of control groups 1 and 2, the retention rate of tobacco sheets of Examples 1-5 is higher; compared with control group 1, the retention rate of tobacco sheets prepared by the calcium carbonate suspensions of Examples 2, 4 and 5 is increased by 3.49-5.23%, and the bulk thickness is increased by 6.96-8.44%; compared with control group 2, the retention rate of tobacco sheets prepared by the calcium carbonate suspension of Example 3 is increased by 3.62%, and the bulk thickness is increased by 12.29%. In summary, during the production process, the calcium carbonate in the calcium carbonate suspension is more easily retained in the tobacco sheet product. Due to the increase in the retention rate of calcium carbonate, the bulk thickness of the tobacco sheet is also increased.

[0137] Bulk thickness detection and calculation: (thickness / quantity)*1000. For thickness detection, refer to the technical standard "GB / T451.3-2002 Paper and paperboard thickness determination", and for quantitative detection, refer to the technical standard "GB / T451.2-2023 Paper and paperboard part 2: quantity"

[0138] Calculation of retention rate: absolute dry weight of reconstituted tobacco leaves / absolute dry weight of (tobacco slurry + filler)*100%.

[0139] Example 6

[0140] In this embodiment 6, the inorganic filler is silica powder to prepare and obtain a calcium carbonate suspension, including the following:

[0141] 1) With a mass ratio of calcium carbonate / inorganic filler of 3:1, silica powder with a particle size of 0.2 μm and water were stirred and mixed for the first time at 30° C. for 5 min to prepare a silica powder slurry; based on the total mass of silica powder and water, the mass concentration of silica powder in the silica powder slurry was 1 wt %.

[0142] 2) Weigh 1 kg of light calcium carbonate with a particle size of 1 μm and 1.22 kg of silica powder slurry from step 1) and stir and mix them for a second time at 30° C. for 5 min to prepare a calcium carbonate suspension; based on the total mass of the inorganic filler, calcium carbonate and solvent, the total mass concentration of the inorganic filler and calcium carbonate in the calcium carbonate suspension is 45 wt %.

[0143] Meanwhile, water and light calcium carbonate with a particle size of 1 μm were mixed at 30° C. for 5 min to prepare calcium carbonate slurry, which was used as control group 3; based on the total mass of calcium carbonate and the solvent, the mass concentration of calcium carbonate in the calcium carbonate slurry was 45 wt %.

[0144] The calcium carbonate suspension of step 2) of the present application and the calcium carbonate slurry of control group 3 were placed for 40 minutes and photographed for observation. The results are shown in Figure 2 ; and tested its consistency, the results are shown in Table 10.

[0145] from Figure 2 As can be seen from the middle left figure, in the control group 3, no inorganic filler was added, and stratification occurred, with calcium carbonate deposited at the bottom.

[0146] from Figure 2 As can be seen from the middle right figure, the calcium carbonate suspension of Example 6, although slightly precipitated, is in the form of an emulsion as a whole.

[0147] Table 10

[0148] Control group 2 Example 6 reduce% Thickness(g.sec) 732.5 525.1 28.310

[0149] It can be seen from Table 7 that the consistency of the calcium carbonate suspension formed by adding inorganic fillers is reduced by 28.31%.

[0150] The calcium carbonate suspension obtained in Example 6 and the calcium carbonate slurry of Control Group 3 were added to the tobacco coating liquid and the tobacco base paper respectively, and the tobacco coating liquid was coated on the tobacco base paper to prepare a tobacco sheet. The specific operation is as follows:

[0151] i) mixing tobacco stems, tobacco flakes and tobacco dust in a mass percentage of 50%:30%:20% to obtain a mixed tobacco raw material, adding 65° C. hot water in a mass ratio of 1:6 between the mixed tobacco raw material and water to perform extraction for 40 minutes;

[0152] ii) After the extraction is completed, the material is mechanically squeezed to separate the solid and liquid, and the separated solid phase is processed by a pulping process to prepare a tobacco slurry, the beating degree of the tobacco slurry is 52°SR, and then the calcium carbonate suspension of Example 6 is added to the tobacco slurry at 10% of the absolute dry weight of the tobacco slurry, and then based on the papermaking process, a tobacco base paper is produced, and the base paper basis weight is 60g / m 2 The separated liquid mixture was concentrated and dehydrated to obtain a density of 1.185 g / cm 3 The tobacco extract is weighed, and the calcium carbonate suspension of Example 6 is added to the tobacco extract according to 7% of the weight of the tobacco extract to prepare a tobacco coating liquid;

[0153] iii) applying the tobacco coating liquid obtained in ii) to the surface of the tobacco base paper obtained in ii) at a coating rate of 38%, and finally drying at 120° C. for 3 minutes to obtain tobacco sheets.

[0154] Meanwhile, the calcium carbonate in the control group 3 was substituted for the calcium carbonate suspension in Example 6 to prepare tobacco base paper and tobacco coating liquid, and to prepare control tobacco sheets, the preparation method of which was the same as that of the calcium carbonate suspension.

[0155] The tobacco coating liquids formed by the calcium carbonate suspension and the calcium carbonate slurry of the control group 3 were left to stand for 40 minutes and photographed for observation. The results are shown in Figure 3; At the same time, the consistency of the tobacco coating liquid was tested, and the results are shown in Table 11; the test results of the bulk and retention rate of the final tobacco sheet are shown in Table 12.

[0156] from Figure 3 As can be seen from the middle left figure, the tobacco coating liquid of the control group 3 showed stratification and precipitation due to the aggregation of calcium carbonate particles.

[0157] from Figure 3 As can be seen from the middle right figure, the tobacco coating liquid of Example 6 is still evenly distributed without stratification or precipitation, and the whole is coffee-like.

[0158] Table 11

[0159] Control group 2 Example 6 reduce% Thickness / (g.sec) 465.8 380.7 18.27

[0160] It can be seen from Table 7 and Table 11 that the tobacco coating liquid formed from the calcium carbonate suspension still has a lower consistency and better fluidity. When the tobacco coating liquid is formed from the calcium carbonate slurry, the consistency decreases from 693.1 g to 465.8 g; when the tobacco coating liquid is formed from the calcium carbonate suspension, the consistency decreases from 432.5 g to 380.7 g.

[0161] Table 12

[0162] Control group 2 Example 6 improve% Retention rate / % 88.50 92.5 4.52% <![CDATA[Bulk thickness cm 3 / g]]> 1.921 2.137 11.24%

[0163] As can be seen from Table 12, compared with the tobacco flakes formed by calcium carbonate and water, the retention rate and bulk of the tobacco flakes formed by the calcium carbonate suspension of the present invention are increased by 4.52% and 11.24% respectively. Therefore, the calcium carbonate suspension of the present invention has a low consistency, can avoid agglomeration, precipitation, and stratification, and the retention rate and bulk of the tobacco flakes obtained are higher, which helps to improve the physical strength and integrity of the tobacco flakes, and can provide better combustion performance when burning.

[0164] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A calcium carbonate suspension, characterized in that, The invention comprises calcium carbonate, inorganic filler and solvent, wherein the mass ratio of the calcium carbonate to the inorganic filler is (3-19):1, and the inorganic filler is selected from one or more of talcum powder, silica powder, barium sulfate, kaolin and titanium dioxide.

2. The calcium carbonate suspension as claimed in claim 1, characterized in that The calcium carbonate is selected from light calcium carbonate; And / or, the particle size of the calcium carbonate is 1 to 10 μm; And / or, the particle size of the inorganic filler is ≤61 μm; And / or, the solvent is selected from one or both of water and ethanol.

3. The calcium carbonate suspension as claimed in claim 1, characterized in that The particle size of the talc is 2 to 6 μm; And / or, the particle size of the silica powder is 0.1 to 0.3 μm; And / or, the particle size of the barium sulfate is 0.1 to 0.5 μm; And / or, the particle size of the kaolin is 0.20 to 0.25 μm; And / or, the particle size of the titanium dioxide is 1.0 to 8.0 μm.

4. The calcium carbonate suspension as claimed in claim 1, characterized in that Based on the total mass of the inorganic filler, calcium carbonate and the solvent, the total content of the inorganic filler and calcium carbonate is not less than 35 wt %, preferably 35 to 55 wt %.

5. The calcium carbonate suspension as claimed in claim 1, characterized in that Compared with a mixture of calcium carbonate and a solvent, the consistency of the calcium carbonate suspension is reduced by at least 7%.

6. A method for preparing a calcium carbonate suspension as described in any one of claims 1 to 5, characterized in that: The steps include: The inorganic filler, calcium carbonate and solvent are mixed to obtain the calcium carbonate suspension.

7. The preparation method according to claim 6, characterized in that: The method comprises the following steps: an inorganic filler and a solvent are mixed for the first time to obtain an inorganic filler slurry, and then the inorganic filler slurry is mixed with calcium carbonate for the second time to obtain the calcium carbonate suspension.

8. Use of the calcium carbonate suspension as described in any one of claims 1 to 5 as a raw material in tobacco sheets.

9. A tobacco sheet comprising tobacco base paper, characterized in that: The tobacco-based paper comprises the calcium carbonate suspension according to any one of claims 1-5.

10. The tobacco sheet according to claim 9, characterized in that: The invention also comprises a tobacco coating liquid, wherein the tobacco coating liquid comprises the calcium carbonate suspension according to any one of claims 1 to 5.